Cancer‐Associated Malnutrition and CT‐Defined Sarcopenia and Myosteatosis Are Endemic in Overweight and Obese Patients. Issue 2 (22nd April 2019) - Martin, Lisa; Gioulbasanis, Ioannis; Senesse, Pierre; Baracos, Vickie E.
Abstract: Background: Overweight/obese patients' large fat mass can mask the loss of skeletal muscle, which is associated with mortality in the oncology setting. We investigated the prevalence of computed tomography (CT)‐defined sarcopenia and myosteatosis across different levels of nutrition risk assessed by the Patient‐Generated Subjective Global Assessment Short Form (PG‐SGA SF). We also evaluated whether the PG‐SGA SF, sarcopenia, and myosteatosis were prognostic of overall survival. Methods: This was a prospective, observational study. Consecutive patients with body mass index ≥25.0 kg/m 2 with newly diagnosed head and neck cancer (any stage) or lung and gastrointestinal tract cancer (locally recurrent or metastatic) were screened at presentation to oncology clinics. Nutrition risk was assigned based on PG‐SGA SF triage recommendations. Based on CT, patients were classified with sarcopenia and/or myosteatosis using published cutoffs. Survival analyses were conducted. Results: Patients (n=1157) were 63.6 ± 11.4 years, 64% male, and 61% had stage IV disease. Sarcopenia and myosteatosis were prevalent across PG‐SGA SF nutrition risk categories (scores 0–1 [no risk; 36% sarcopenic; 44% myosteatotic], scores 2–3 [37%; 37%], scores 4–8 [40%; 41%], and scores ≥9 [high risk; 50%; 49%]). In multivariable survival analysis, PG‐SGA SF scores ≥9 (hazard ratio [HR] 2.08, 95% confidence interval [CI] 1.66‐2.60, P <0.001), sarcopenia (HR 1.25, 95% CI 1.06‐1.46, P =0.006), and myosteatosis (HR 1.25, 95% CI 1.07‐1.46, P <0.001) independently predicted reduced survival. Conclusion: CT‐defined sarcopenia and myosteatosis are prevalent across different levels of nutrition risk in overweight/obese patients with cancer. Assessment of skeletal muscle using CT adds prognostic value to the PG‐SGA SF.